THE ENVIRONMENTAL PERFORMANCE OF AGRICULTURAL FARMS IN RELATION TO THEIR SECTOR AND PRODUCTION SYSTEM - M. Topchieva (Trakia Journal of Sciences)
Greenhouse gas emissions, nitrogen and phosphorus emissions to water, air and soil are agriculture’s main environmental externalities, which contribute to significant negative impacts, such as climate change, water and terrestrial eutrophication and loss of biodiversity, among others. The environmental performance of agricultural farms differs significantly depending on the sector, on the production system, and on the applied production practices. Therefore, the potential for reduction of the farms’ negative environmental impacts varies significantly. By means of literature review and analysis, the article aims to present an overview of the environmental impacts of the agricultural farms, considering their sector and production system. As a result, an outline of farms with the lowest to highest negative environmental impact is presented. This distinction allows for further analysis of the factors contributing to the most polluting and resource-intensive production practices in agriculture. In conclusion, mitigation potentials and opportunities for improving the environmental performance of farms are given, with relevance to the specific sectors and production systems.